Application of full factorial design to control the size of bisphenol a molecular imprinted polymer - Nurul Shareena Aqmar, Mohd Sharif (2013)
Molecular imprinted polymer (MIP) has caught the attention of many researchers in recent years as a great tool for molecular recognition and other applications. However, the main issue in the synthesis of MIP nanoparticles is the identification and optimization of the main factors affecting the particle size. This study described two objectives; first, to control the particle size of MIP using an experimental design analysis, secondly to synthesize MIP nanoparticles with recognition of Bisphenol A (BPA). Sixteen sets of BPA-MIP particle with three center point replications were produced according to factor combination set by Design Expert Software. The analysis was aimed at the relationship of four selected parameters: the polymerisation temperature, agitation rate, solvent to crosslinker ratio, and percentage of initiator. Almost all obtained particle sizes were in the range of 90 to 160 nm, but the smallest size obtained was 30nm, and the largest size was 2 µm. Polymerization temperature was the most significant factor, followed by solvent to crosslinker ratio, agitation rate and percentage of initiator. Two-way interaction of polymerization temperature and solvent to crosslinker ratio was also found to be highly significant in affecting BPA-MIP. An acceptable value for R2 presented from ANOVA analysis is 0.9770. The characterization studies also support a good rigidity and stable thermal properties of BPA-MIP particles. Resultant BPA-MIP copolymers had BPA binding capacity ranging from 77.74 to 102.26 µmol/g. The highest binding of BPA was MIP 15 at 100 nm particle size, with 102.26 µmol/g, while the lowest BPA binding of 77.74 µmol/g was achieved from MIP 16 with the same size. It can be concluded that the smaller the size of imprinted polymer, does not necessarily improved its binding ability. The selected optimum condition of BPA-MIP synthesis was MIP 15 due to its highest binding capacity, which was synthesized at 45 oC, no agitation, 50 % of solvent to crosslinker ratio and 1% of initiator. In overall, experimental design approach used in this study could, overcome tedious procedure involves in controlling the size of BPA-MIP within the nano size. Nano size BPA-MIP is required to produce high performance hybrid MIP membrane that can be easily handle and operate. This MIP technique can be further extended to any other template for different applications.